Komunikasi Pemasaran Objek Wisata Peninggalan Belanda Swimbath Kabupaten Simalungun Dalam Meningkatkan Jumlah Pengunjung - Arrizki, Defara Tria (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
Swimbath is a natural bathing area located within the PTPN4 Emplasmen Laras plantation, offering a refreshing and captivating experience for visitors. With a tranquil and peaceful atmosphere, swim bath allows visitors to relax while enjoying the stunning natural scenery. The purpose of this writing is to provide an overview of the marketing communication strategies implemented to increase the number of visitors. This writing employs a qualitative descriptive method, focusing on open interviews to understand the attitudes, views, feelings, and behaviors of individuals or groups related to swim bath. The primary informants are the administrators of the Swim bath natural bathing attraction in Simalungun Regency, Bandar Huluan District, including the Chairman of SPBUN Emplasmen Laras, daily administrators, and several local residents involved in the management of swim bath. Although Swimbait’s promotional strategy has not included conventional advertising, its popularity has increased in North Sumatra, particularly in Simalungun and Siantar City. The main strategies include direct engagement with visitors by introducing attractive spots and dining options within the area, and expanding reach through social media. Efforts to establish Swimbath as a family-friendly destination are ongoing, with a focus on safety and avoiding illegal charges.